2018
DOI: 10.3889/oamjms.2018.381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lower-Limb Endurance Training on Dyspnea and Lung Functions in Patients with COPD

Abstract: BACKGROUND:Patients with chronic obstructive pulmonary disease (COPD) exhibit persistent dyspnea in daily activities and irreversible airflow obstruction. These will finally lead to an inability to carry on daily activities and markedly decrease their quality of life. Endurance training was considered as therapy modality to alleviate several symptoms experienced by COPD patients.AIM:This study aims to identify the impact of lower-limb exercise on dyspnea and spirometry test results in COPD patients.METHODS:We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
10
0
4
Order By: Relevance
“…[ 38 ] A study showed that LL endurance training twice a week for 1 month improved dyspnea and pulmonary function test results safely and effectively in patients with COPD. [ 39 ] However, a meta-analysis confirmed that a combination of resistance and endurance trainings increases leg muscle strength, health-related quality of life, walking distance, and exercise capacity in patients with COPD, but none of the included studies investigated their combined effect on the level of dyspnea. [ 40 ] The results of LL training mainly showed its influence on muscle strength and endurance, and most studies have not reported on the effects of the training on dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] A study showed that LL endurance training twice a week for 1 month improved dyspnea and pulmonary function test results safely and effectively in patients with COPD. [ 39 ] However, a meta-analysis confirmed that a combination of resistance and endurance trainings increases leg muscle strength, health-related quality of life, walking distance, and exercise capacity in patients with COPD, but none of the included studies investigated their combined effect on the level of dyspnea. [ 40 ] The results of LL training mainly showed its influence on muscle strength and endurance, and most studies have not reported on the effects of the training on dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several high‐quality clinical studies have verified the benefits of pulmonary rehabilitation for inpatients, outpatients, and in–home patients. The benefits include improved exercise tolerance in patients with chronic pulmonary diseases, reduced number of hospital admissions and length of hospital stays, enhanced health‐related quality of life, 5 improved respiratory muscle function and relieved dyspnea, 6 alleviated disease‐related anxiety and depression, 7 and enhanced skeletal muscle function of upper and lower limbs 8 , 9 …”
Section: Pulmonary Rehabilitationmentioning
confidence: 99%
“…Patient was able to maintain an oxygen saturation of 99% on room air by the 3 rd day of intervention. There was also an 118% increment in 30SSTS score when compared to day 1, which shows improvement in muscle endurance and exercise tolerance [16,17] following regular physiotherapy; Endurance training has shown to be a useful modality to alleviate symptoms in patients with COPD by showing improvements in dyspnoea and pulmonary function tests [18]. This 28-year-old, physically active individual admitted in the isolation facility showed excellent response to the intervention, as evident by the outcome measures ( [24] observed that healthy individuals will have a predicted 6MWD of 631 ±93meter.…”
Section: Discussionmentioning
confidence: 99%